Determination of endophytic organisms in seeds of j. Curcas l and j. Macrocarpa griseb (International Seven Journal of Multidisciplinary, 2024)
Endophytes are microorganisms that reside all or part of their lives in plant tissues in a symbiotic, parasitic or mutualistic relationship, without immediately causing negative effects (Stone et al., 2000). As a result of such long-standing associations, endophytic microorganisms and plants have developed a great deal of information transfer (Strobel and Daisy, 2003). Certain medicinal plants synthesize chemicals, providing material for the pharmaceutical and cosmetic industry (Karthikeyan et al., 2008) and endophytes participate in metabolic pathways of these plants and produce bioactive compounds (Zhao et al., 2011).